2019
DOI: 10.14336/ad.2018.1216
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea Facilitates Manifestation of Disease Relevant Phenotypes in Patients-Derived IPSCs-Based Modeling of Late-Onset Parkinson’s Disease

Abstract: Induced pluripotent stem cells (iPSCs)-derived dopaminergic neurons might be reset back to the fetal state due to reprogramming. Thus, it is a compelling challenge to reliably and efficiently induce disease phenotypes of iPSCs-derived dopaminergic neurons to model late-onset Parkinson’s disease (PD). Here, we applied a small molecule, hydroxyurea (HU), to promote the manifestation of disease relevant phenotypes in iPSCs-based modeling of PD. We established two iPS cell lines derived from two sporadic PD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Using a well-established midbrain DA neuron differentiation protocol with some minor modifications 19,20 , we successfully generated the floor plate (FP) cells and mature A9 group DA neurons from control and PLA2G6 D331Y/D331Y iPSCs (Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a well-established midbrain DA neuron differentiation protocol with some minor modifications 19,20 , we successfully generated the floor plate (FP) cells and mature A9 group DA neurons from control and PLA2G6 D331Y/D331Y iPSCs (Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
“…1a). Human UC-H1-iPSCs established in our previous study served as the controls 19,20 . Group A9 is the most densely packed group of DA neurons in the ventrolateral midbrain.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of progerin to induce aging in iPSC-derived DA neurons from patients with PD promotes PD disease phenotypes [ 94 ]. Hydroxyurea-treated DA neurons from patients with sporadic PD can rapidly produce PD-related manifestations in early stages [ 95 ]. These strategies facilitate the manifestation of disease-relevant phenotypes in a PD model based on iPSCs derived from patients.…”
Section: Cellular Models For Pdmentioning
confidence: 99%
“…Previous studies have indicated that chronic treatment with anticancer drug hydroxyurea (HU) could induce cellular senescence in human fibroblasts[106] and mouse neural stem cells[107] via induction of genes related to DNA damage and repair, mitochondrial dysfunction, and ROS increase. In our recent study[108], we found that HU induced disease phenotypes of sporadic PD-patient-specific iPSC-derived DA neurons. HU treatment significantly reduced neurite outgrowth, expression of p-Akt and its downstream targets (p-4EBP1 and p-ULK1), as well as increased the level of cleaved caspase 3 in iPSC-derived DA neurons from sporadic PD patients.…”
Section: Challenges In Using Ipscs To Model Pdmentioning
confidence: 99%